PELATIHAN BAHASA INGGRIS UNTUK PEMANDU WISATA: MENINGKATKAN DAYA SAING WISATA DI DESA WARNASARI, PANGALENGAN JAWA BARAT - Dariyanto, Dariyanto; Natalia, Inpresta; Sobarli, Utep; Chalisyah, Elis; Adrianty, Desi (JURNAL ABDIMAS PLJ, 2025)
English Training for Tour Guides is a strategic effort to increase the capacity of local human resources and the competitiveness of the tourism sector in Desa Warnasari, Kecamatan Pangalengan, Kabupaten Bandung, West Java. Desa Warnasari has attractive natural tourism potential, but still faces challenges in reaching foreign tourists due to limited communication skills in foreign languages, especially English. This training activity aims to equip residents and youth organizations who become local tour guides with basic English skills relevant to the world of tourism, such as introducing tourist attractions, explaining travel routes, answering visitors' questions, and conveying local cultural and historical information. The training methods used include interactive lectures, hands-on practice (role play), and questions and answers. The results of the training showed a significant improvement in the confidence and communication skills of participants in English. With this training, it is hoped that tour guides can provide more professional services to foreign tourists, as well as encourage an increase in the number of visits and tourist satisfaction, which will ultimately strengthen the position of Desa Warnasari as a leading tourist destination in the Pangalengan area.